EFFECT OF NANOSILICA AS AD-MIXTURE IN LIGHT WEIGHT CONCRETE - Sulaiman, Tasiu Ashiru; Yau, Y.; Hashim, Y. M. (FUDMA Journal of Sciences, 2023)
This paper is aimed at assessing the effect of Nano silica on compressive strength and durability properties of lightweight concrete made with waste burnt bricks as coarse aggregate, using a mix ratio of 1:2:4 and water/cement ration of 0.6. Preliminary tests such as sieve analysis, specific gravity, bulk density, water absorption and aggregate impact value were conducted on brick aggregate and the results were compared to that of coarse aggregate. The workability of freshly prepared burnt bricks-concrete and normal concrete were determined, 45 cubes were cast and cured for a period of 3 days, 7 days, and 28 days respectively. The result of compressive strength test obtained show that concrete made with waste burnt bricks as an aggregate has a compressive strength of 10.9 N/mm2 and 17.57 N/mm2at 0 % and 3 % Nano silica addition respectively, this means the compressive strength of the concrete is affected by increasing the percentage of Nano silica. Whereas the compressive strength of the concrete with coarse (granite) aggregate was found to be 26 N/mm2, this indicates that concrete made with waste burnt bricks can be used in structural work where high strength is not of paramount importance such as ground floor slab, ramps, partition wall etc.
Keywords: Light weight concrete, Nano-silica, waste broken, burnt bricks, compressive strength